Determination of antibodies against serovars of Leptospira spp in guinea pigs of family-commercial breeding in Cajabamba, Peru - Gutiérrez A., Amanda (2020)
The aim of this study was to determine antibodies against five serovars of Leptospira spp in guinea pigs of family-commercial breeding in Cajamarca, Peru. Blood samples were collected from 242 apparently healthy guinea pigs destined for consumption on five farms. The sera were processed using the microagglutination test (MAT), considering titers >1/100 as seropositive. Reference strains from the serovars Bratislava, Canicola, Hardjo, Icterohaemorrhagiae and Pomona were used. Seroprevalences of 40.50% (98/242) (95% CI: 34.3-46.7%) were found to antibodies against Leptospira spp. The reactive serovars were Icterohaemorrhagiae (19.01%, 46/242), Canicola (16.53%, 40/242) and Pomona (8.68%, 21/144). There was no seroreactivity to Bratislava and Hardjo serovars. There was no statistical association with sex or farm. Seropositivity indicates exposure and circulation of Leptospira spp, which represents a public and animal health risk.